“EFEKTIVITAS SOSIALISASI ANTI-BULLYING DALAM MENINGKATKAN PEMAHAMAN DAN KEPEDULIAN SISWA MTS NEGERI 4 LANGKAT” - Indira Fatra Deni; Roy Rayyan Manandha Ginting; Najwa Zahra; Khadizah Rania Cahyani Damanik (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the effectiveness of anti-bullying socialization in improving students’ understanding and empathy in schools. The background of this research is the persistence of bullying cases that cause negative impacts on students’ psychological, social, and academic development. Schools, as formal educational institutions, have an important responsibility to conduct preventive efforts, one of which is through anti-bullying programs. This research employed a descriptive quantitative method with a questionnaire distributed via Google Form. The population consisted of junior high school students, with 80 respondents selected through purposive sampling. The questionnaire consisted of 10 items measuring aspects of understanding, social awareness, and students’ assessment of the program. Data were analyzed using frequency distribution and percentages. The findings revealed that the majority of respondents, more than 80 percent, chose strongly agree and agree across all indicators. Most students stated that they understood the definition and types of bullying, knew appropriate actions to take when witnessing bullying, and perceived the material as easy to understand. Furthermore, respondents admitted to feeling more empathetic toward peers and committed not to engage in bullying after the program. The success of the socialization was also influenced by the clarity, communicative delivery, and engaging presentation of the material. Another key finding is that students strongly supported the idea of conducting such programs regularly in schools